Owly. The way home & the bittersweet summer - Runton, Andy. (Marietta, Ga. : Top Shelf, 2004)
Owly, a kind, lonely owl, helps and then befriends first a worm and then a pair of hummingbirds in these two nearly wordless stories.
GN390L
3-6
2.0
Keywords: Owls -- Juvenile fiction; Owls -- Fiction; Birds -- Fiction; Cartoons and comics; Friendship -- Fiction; Graphic novels; Comics (Graphic works)